Research Progress of Deoxygenation Functional Materials in the Field of Food Preservation - HUANG Qi-yan; LAN Yu-fei; WU Shu-fen; YANG Wei-qiao; WANG Wen -juan; DUAN Xiao-liang; YU Shang-ke (Liang you shipin ke-ji)
Functional deoxygenation materials (including oxygen scavengers and deoxygenation packaging) have the potential to reduce the oxygen content inside the packaging and establish a low-oxygen micro- environment, which is of great research value and application potential for prolonging the shelf-life of food and ensuring food safety. Based on the diversity of physical properties of functional deoxidation materials, this paper firstly introduces various types of deoxidants, deoxidation films and their deoxidation mechanisms based on the different deoxidation modes of deoxidation materials, the differences of deaeration efficiency of various deaeration materials were analyzed, compares the advantages and disadvantages of the commonly used film preparation techniques, reviews the research progress in the field of research and development of deoxidation materials at home and abroad and their applications in food, and summaries and looks forward to the challenges and development of food preservation based on deoxidation functional materials. The review provides a reference to keep abreast of the research status of new functional materials for food and to promote the technological innovation and application of deoxidation materials for food.